2011
DOI: 10.4254/wjh.v3.i10.265
|View full text |Cite
|
Sign up to set email alerts
|

Role of ezetimibe in non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) encompasses a histological spectrum ranging from simple steatosis to steatohepatitis, advanced fibrosis and inflammatory changes. Ezetimibe inhibits cholesterol absorption from the intestinal lumen into enterocytes. The molecular target of ezetimibe is the sterol transporter Niemann-Pick C1-like 1 protein (NPC1L1). Human NPC1L1 is abundantly expressed in the liver and may facilitate the hepatic accumulation of cholesterol. Ezetimibe exerts beneficial effects on several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…In addition, reactive oxygen species (ROS), endotoxins, and inflammatory cytokines result in the disease development [7]. It is also well known that several stressors like cigarette smoke, pollutants, diabetes, hypertension, and hypercholesterolemia are all risk factors to the disease [8, 9]. The hepatic insulin resistance state of fatty liver infiltration is characterized by increased free fatty acids (FFAs), which causes lipotoxicity, impairs endothelium-dependent vasodilatation, and increases oxidative stresses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reactive oxygen species (ROS), endotoxins, and inflammatory cytokines result in the disease development [7]. It is also well known that several stressors like cigarette smoke, pollutants, diabetes, hypertension, and hypercholesterolemia are all risk factors to the disease [8, 9]. The hepatic insulin resistance state of fatty liver infiltration is characterized by increased free fatty acids (FFAs), which causes lipotoxicity, impairs endothelium-dependent vasodilatation, and increases oxidative stresses.…”
Section: Introductionmentioning
confidence: 99%
“…This protein is expressed by both enterocytes and hepatocytes. It was suggested that ezetimibe may be useful for the management of NAFLD by inhibiting hepatic cholesterol accumulation [45] . This can be better achieved by combinations of ezetimibe with drugs facilitating weight loss or enhancing insulin sensitivity [45] .…”
Section: Introductionmentioning
confidence: 99%
“…Our patient could not receive a statin due to abnormal liver function. He was instead started on ezetimibe because of its LDL-C lowering effect particularly in the setting of advanced liver fibrosis [4] . Another option for reducing LDL-C in our patient was by LDL apheresis, a technique that has proven to significantly reduce low-density lipoprotein cholesterol in patients with severe hypercholesterolemia and slow the progression of atherosclerosis [5] .…”
Section: Discussionmentioning
confidence: 99%